River-bed evolution during the Holocene in Kalavrita region (northern Peloponnese, Greece). - Stamatopoulos, L.; Evelpidou, N. (Revista de Geomorphologie, 2011)
Environmental history often reveals the contribution of humans in the modification of natural environment, always in relation with the climatic factors. Archaeological settlements may be preserved through desiccation, however, they are commonly found in floodplain sediments. Archaeological evidences may provide with useful information about the processes and extent of environmental changes, but they may also be used as tools for the analysis of floodplain sedimentation, relative chronology of sedimentation events and for the geomorphological evaluation of the particular archaeological site. The characteristics of archaeological indicators and the deposits in which they occur, may indicate important aspects of their source, transportation way and age. Evidence of river migration may be found in alluvial plains, through careful observations. The study area is located in Kalavrita region in northern Peloponnese. The archaeological excavations carried out revealed the fortification wall of the ancient city of "Kleitor"which is dated between the 3rd and 2nd century BC (Hellenistic Period). It may also provide clues for land surface development, reworking of sedimentary deposits, paleoenvironmental and climatic conditions. Sediments indicating considerable climatic changes are alluvial deposits of considerable thickness, covering areas with human impact. All the aforementioned become a tool for dating the course changes of the rivers and consequently a geomorphological instability. The relationship between geomorphology and history is recognizable also in the settlement distribution. This close relationship between environment and man provides a tool to understanding the landscape evolution from a geomorphological and historical point of view.